Dinamika Pendidikan Islam Multikultural Perspektif Tradisi dan Perkembangan Pesantren di Indonesia - Zainullah, Zainullah; Sayyi, Ach (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
The Indonesian nation is composed of a number of cultural, ethnic, racial, and religious groups, so that the Indonesian nation can be grouped or categorized as a diverse (multicultural) society. One of indicator is the diversity of ethnic, culture, and religion where Islam is the majority religion. The growth and development of Islam in Indonesia rises from the role of Islamic educational institutions such as madrasah and pesantren. This article will be briefly explained about; 1) pesantren and its development; 2) the tradition of pesantren as picture of Islam in Indonesian, and 3) multicultural values ​​in pesantren. This is important to know as the focus of the discussion in this article. To uncover and explain the three focus above, it must be supported through several theories as a poin of analysis, namely about pesantren, pesantren traditions, and multicultural values. The method of writing this article is through a qualitative approach, while the type of research is theoretical-descriptive based on library research. The results of the research are that; a) historical perspective of pesantren as a friendly, tolerant face of Indonesian Islam able to survive for centuries and give color to this age; b) some of the pesantren traditions, among others, are local wisdom in the form of value systems and social interactions are meaningful because they are formed from the pesantren community itself and are sourced from religious forces; c) the values ​​of pesantren multiculturalism can be seen through local wisdom, such as marriage, kinship, family harmony, frienship, fostering brotherhood (ukhuwah), visiting the sick, caring for orphans, mutual cooperation, solidarity, mutual respect, promoting dialogue, moderate and tolerant.